Síntese de nanopartículas para entrega direcionada de 5-fluorouracil no tratamento do câncer colorretal - Sanchez, Ana Laura Moreno Martins (Universidade Federal de São Carlos, 2025)
: Colorectal cancer is the second most lethal, surpassed only by lung cancer. In Brazil, the number of cases is expected to increase over the next three years, with women being the most affected. 5-Fluorouracil (5-FU) is one of the most used drugs for colorectal cancer treatment, but it causes numerous side effects. To overcome these limitations, one innovative strategy is the use of controlled release systems. Poly(lactic-co-glycolic acid) (PLGA) polymeric nanoparticles are among the most employed systems for this purpose due to their biodegradability and biocompatibility. Three different synthesis methods were used to obtain the nanoparticles (NPs): nanoprecipitation, single emulsion, and double emulsion. The results demonstrated that the synthesis methodologies employed were suitable for producing nanoparticles with sizes below 300 nm, PDI lower than 0.2, and a negative zeta potential around -30 mV, with SEM images showing spherical shapes. Furthermore, 5-FU suggests a controlled and efficient release, and with the double emulsion technique, an encapsulation efficiency of 71.4% was achieved. FTIR analysis showed that the incorporation of 5-FU did not cause significant changes in the functional groups of PLGA, indicating preservation of the carrier’s chemical structure. Additionally, the NPs were not cytotoxic to CACO-2 cells in the absence of the drug, demonstrating good biocompatibility, and confocal microscopy indicated that most nanoparticles were internalized. Therefore, it is expected that 5-FU-loaded nanoparticles may improve drug efficacy and targeting, contributing to the development of alternative therapies against colorectal cancer.
Synthesis of nanoparticles for targeted delivery of 5-fluorouracil in colorectal cancer treatment
Keywords: Câncer colorretal; Síntese de nanopartículas; PLGA; 5-Fluorouracil; CIENCIAS BIOLOGICAS::FARMACOLOGIA::FARMACOLOGIA GERAL::BIODISPONIBILIDADE; CIENCIAS BIOLOGICAS::FARMACOLOGIA; CIENCIAS BIOLOGICAS::BIOQUIMICA::QUIMICA DE MACROMOLECULAS::PROTEINAS; CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA::CANCEROLOGIA; CIENCIAS DA SAUDE; 3. Saúde e Bem-Estar